PARTISIPASI MASYARAKAT DALAM MENGEMBANGKAN DESA WISATA GEDEPANGRANGO - Noval Maliki; Nirvana Adelia Trisna (Mimbar Administrasi Mandiri, 2023)
This research is motivated by community participation issues found in the presurvey, which include the role of information, leadership, local organizations, and village government in the development of tourism villages in Gedepangrango Village, Sukabumi District. This research aims to (1) understand the role of information, (2) evaluate leadership, (3) examine the role of local organizations, and (4) assess the role of village government in community participation. This research adopts Kurniantara and Pratikno's theory, which identifies the role of information (including forms of information and information media), leadership (involving leadership patterns), the role of local organizations (related to organizational duties and functions), and the role of village government (focusing on coordination and collaboration with related agencies). This research methodology is qualitative using a descriptive approach. Data were collected through interviews, observations, and documentation, then analyzed by data reduction, data presentation, and conclusion drawing. Four informants were selected using purposive sampling and snowball sampling techniques. The research objects included the Head of Gedepangrango Village, the Pokdarwis Supervisor, and two local communities involved in tourism development. The results showed that community participation in tourism village development has not been optimal. Influencing factors include the lack of an effective information role, inadequate leadership, unclear roles of local organizations, and a fairly good role of the village government. The conclusion of this study is that because some indicators of each dimension are still not appropriate, community participation in tourism village development in Gedepangrango Village, Sukabumi District, has not been well achieved.